2015
DOI: 10.1097/qad.0000000000000725
|View full text |Cite
|
Sign up to set email alerts
|

Sankofa

Abstract: With the scale-up of effective antiretroviral therapy in resource-limited settings, many HIV-infected children are now able to survive into adulthood. To achieve this potential, children must navigate normative developmental processes and challenges while living with an unusually complex, stigmatizing, potentially fatal chronic illness and meeting the demands of treatment. Yet many of these children, especially preadolescents, do not know they are HIV-infected. Despite compelling evidence supporting the merits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…It might reflect that disclosure is a gradual process and caregivers’ recognition about its completion is sometimes vague. This means that long-term periods’ cooperation between caregivers and healthcare providers, as the previous studies pointed out [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 84%
“…It might reflect that disclosure is a gradual process and caregivers’ recognition about its completion is sometimes vague. This means that long-term periods’ cooperation between caregivers and healthcare providers, as the previous studies pointed out [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 84%
“…WHO has also published the Guideline on HIV Counseling for Children up to 12 years of Age for adaptation in countries ( 5 ). Existing pediatric disclosure models and tools, such as children’s books, videos, job aides, and curricula, aim to assist health care providers, caregivers, and/or children in disclosure ( 37 39 ). These models and tools also address some of the health outcomes identified in this review.…”
Section: Discussionmentioning
confidence: 99%
“…These models and tools also address some of the health outcomes identified in this review. For instance, the SANKOFA disclosure model, which is family-centered, clinic-based, and health worker facilitated, addresses adherence, viral and immunologic markers, and mental health outcomes ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beck-Sague et al [36] reported promising results of an ongoing quasi-experimental trial of a culturally adapted paediatric HIV disclosure intervention in Haiti, which included healthcare worker training, education for youth, capacity-strengthening for caregivers, a scheduled disclosure session and postdisclosure support for care-givers and youth. Equally reporting on an ongoing study, Reynolds et al [37] presented the background, process and methods of a collaborative approach to develop and evaluate a paediatric HIV disclosure intervention in Ghana; challenges and implications are also reported. Brandt et al [38] undertook a qualitative study to identify the key components of a child-friendly ‘disclosure book’ to assist caregivers and healthcare workers in Namibia with paediatric HIV status disclosure.…”
mentioning
confidence: 99%